Validation of an instrument to measure the knowledge, behavior and perception regarding tuberculosis - Roa Chunga, Luis Alejandro (2025)
The survey, as a research instrument, is vital for collecting and obtaining data in an orderly and effective manner. The objective of the study was to validate an instrument for collecting reliable and valid data on the knowledge, behavior and perception of patients with tuberculosis. The study was descriptive and cross-sectional with a design that included validation in two stages. First, consensus was reached among six experts regarding a 21-item questionnaire, which evaluated three dimensions: knowledge (12 items), behavior (3 items) and perception (6 items). Second, a pilot test was conducted with a sample of 30 patients to assess the categories of sufficiency, clarity, coherence and relevance. As to the values of sufficiency and relevance, 19 out of 21 items (90.5 %) matched, indicating a high level of adequacy and relevance, with an Aiken’s V value of 0.981429. At the clarity level, 18 out of 21 items (85.7 %) matched, indicating a high level of comprehensibility, with an Aiken’s V value of 0.970952. As to coherence, 18 out of 21 items (85.7 %) matched, indicating a high level of consistency, with an Aiken’s V value of 0.98381. The reliability, measured by Cronbach’s alpha, was 0.95 for knowledge, 0.83 for behavior and 0.89 for perception. It is concluded that the validated instrument at the Hospital Militar Central measured valid and reliable results regarding the knowledge, behavior and perception of tuberculosis.